Politik Pork Barrel di Indonesia: Kasus Hibah dan Bantuan Sosial di Provinsi Banten tahun 2011 - Saragintan, Antonius; Hidayat, Syahrul (UI Scholars Hub, 2016)
The populist programs deployed by government have a higher degree of being used as strategy to increase support at elections known as pork barrel politics. This paper finds that similar pattern also happened in the allocation of grants and social assistance in the province of Banten provided by the local government. This research aims at ans¬wering the question: can the grants and social assistances allocated by incumbent in Banten Province in 2011 be categorized as pork barrel distributive politics? By using qualitative method, this study unveils a tendency that both allocation of grants and social assistance were utilized as political strategy by targeting the stronghold suppor¬ters of the incumbent as well as some influential religious groups. This research also underlines that the concept of pork barrel can be expanded from its original definition to cover policies initiated by executive and can take place in local rather than national.